The use of Social Networking Sites (SNSs) in health communication campaigns : review and recommendations - Shi, Jingyuan (2019)
The past decade has witnessed a rapid increase in the use of Social Networking Sites (SNSs) in health communication campaigns seeking to achieve an ambitious range of health-related impacts. This article provides a review of 40 studies and research protocols, with a focus on two key factors that differentiate SNSs from more traditional health communication approaches of the past. The first is the potential dualism between message sender and receiver, in which receivers become receiver-sources who forward and amplify the content and reach of health messages. The second is the potential dualism between message and message impact, in which the act of forwarding and modifying messages by receiver-sources itself becomes a measure of message impact. Each of these dualisms has implications for the design and evaluation of contemporary health communication campaigns. The review concludes with a series of observations and recommendations for future health communication research.